The Impact of Aromatherapy with Citrus Aurantium Essential Oil on Sleep Quality in Pregnant Women with Sleep Disorders: A Randomized Controlled Clinical Trial - Freshteh Mohammadi; Maryam Moradi; Azin Niazi; Jamshid Jamali (International Journal of Community Based Nursing and Midwifery, 2022)
Background: Sleep disorders are so prevalent during pregnancy. The present study was conducted to investigate the impact of aromatherapy with Citrus aurantium essential oil on sleep quality in pregnant women with sleep disorders. Methods: This randomized clinical trial study was conducted on 68 pregnant women in their 28-34 weeks of pregnancy who sufferred sleep disorders and referred to Jiroft health centers in 2021 (January-June). Those meeting the inclusion criteria were divided into the intervention and placebo groups, using random sequence generated through the randomization website. They were given five drops of Citrus aurantium essential oil and the placebo twice a day, every day for one month in the form of facemasks which they inhaled through normal breathing for 20 minutes. Sleep quality was assessed before the intervention and one month after the start of the intervention. The demographic questionnaire and Pittsburgh Sleep Quality Index (PSQI) were used for collecting the data. Data analysis was performed using SPSS 24 software. The Mann–Whitney-U, Wilcoxon and fisher exact tests were carried out. P-value<0.05 was considered statistically significant. Results: Before the intervention, the mean and standard deviation scores of pregnant women’s sleep quality in the intervention (9.89±3.00) and placebo (8.12±2.53) groups were not significantly different (P=0.10). One month after the intervention, the score was significantly lower in the intervention group (4.37±1.85) than the placebo group (8.48±2.62) (P<0.001). Conclusion: Based on the results of the present study, it seems that aromatherapy with Citrus aurantium essential oil enhances the sleep quality in pregnant women with sleep disorders, so it can be used to diminish sleep disorders in these women. Trial Registration Number: IRCT20200512047414N1.